The root of thought: unlocking glia the brain cell that will help Us sharpen our wits, heal injury, and treat brain disease - Koob, Andrew
Until recently, neuroscientists thought glial cells did little more than hold your brain together. But in the past few years, they've discovered that glial cells are extraordinarily important. In fact, they may hold the key to understanding intelligence, treating psychiatric disorders and brain injuries and perhaps even curing fatal conditions like Alzheimer's, Parkinson's, and Lou Gehrig's Disease. In The Root of Thought, leading neuroscientist Dr. Andrew Koob reveals what we've learned about these remarkable cells, from their unexpected role in information storage to their function as adult stem cells that can keep your brain growing and adapting longer than scientists ever imagined possible. Ranging from fruit flies to Einstein, Koob reveals the surprising correlation between intelligence and the brain's percentage of glial cells - and why these cells' unique wavelike communications may be especially conducive to the fluid information processing human beings depend upon. You'll learn how crucial glial cells grow and developáginas:.. why almost all brain tumors are comprised of glial cells and the potential implications for treatment... even the apparent role of glial cells in your every thought and dream!